Diástase abdominal, capacidade funcional, estabilidade pélvica e dor lombar em gestantes - Landgraf, Fernanda Massari (2017)
Introduction: As pregnancy advances the influence of relaxin and the pressures exerted by the growing fetus create new relationships between the thoracic and abdominal contents, stretching the abdominal wall. At the height of this situation relaxin may exert additional influence on the Alba line, causing abdominal diastasis. There are innumerable musculoskeletal adaptations and possible constant activation of the posterior trunk chain to compensate for instability, leading to muscle fatigue and low back pain in pregnant women. Objective: To verify the relationship between abdominal diastasis, functional capacity, pelvic stability and low back pain in primigravidae. Method: A cross-sectional study, approved by the Ethics Committee in Research with Human Beings of the University of the Sacred Heart (nº 1,586,483), with healthy primigrates enrolled in the Family Health Strategies of Assis / SP, in the period of August, 2016 to the one of January of 2017. The pregnant women were invited to participate of the research and after the accepted one, they signed the free and informed consent term. The following instruments were used: characterization of the pregnant women (sociodemographic questionnaire), measurement of abdominal diastasis (digital pachymeter), anthropometric data (weight, height, waist circumference), reports of pain (VAS), functional capacity (Oswestry and Roland Morris Questionnaires) and pelvic stability (Biophotogrammetry). Data were submitted to descriptive statistical analysis (mean, standard deviation, maximum and minimum values), as well as absolute and relative frequencies. The associations between abdominal diastasis, functional capacity, lumbopelvic stability and low back pain were performed using the Pearson correlation test. Results: Presence of 100% diastasis in the supraumbilical region, 98% in the infraumbilical region, 84% of the participants presented pain in the low back, 54.9% of moderate intensity (VAS), 31.4% had moderate to severe disability (Questionnaire of Oswestry disabilities), and 80.4% do not consider it disabling when assessed by the Rolland Morris Questionnaire. It was noted moderate correlation (r = 0.50) between infraumbilical DMRA and functional capacity, low correlation (r = 0.43) between the angle of cervical lordosis and abdominal diastasis, and a discrete correlation between abdominal diastasis and visual analogue scale, with r = 0.41 in the infraumbilical region and abdominal diastasis. Conclusion: The results of this study allow us to infer a higher occurrence of abdominal diastasis in the supraumbilical and infraumbilical regions, and the relationship between infraumbilical diastasis and reports of low back pain. Although small but positive, there is a correlation between abdominal diastasis and functional capacity.